Capacity and culpability - Manwaring, J (2019)
How should the criminal law account for defendants’ incapacities? It’s often claimed that some incapacities make individuals less culpable for wrongdoing. But what follows if this is true? Like many others, I claim that the criminal law ought not to convict offenders disproportionately to their culpability. Thus, if incapacities render individuals less culpable, then the criminal law ought to account for that lowered culpability. But rather than accepting this ‘culpability principle’ under the guise of non-instrumentalist retributivism, I instead derive it from instrumental considerations regarding fair labelling.